Walking frame design recommendation based on experience of elderly user, carer, and the industry in Kuala Lumpur & Selangor, Malaysia - Hussain, Mohd Rizal; Haron, Nuzul Azam; Raja Ahmad Effendi, Raja Ahmad Azmeer; Ibrahim, Rahimah; Sulaiman, Ruhaizin; Ahmad, Siti Anom; Rokhani, Fakhrul Zaman; Ashari, Asmidawati; Hassan, Mohd Khair; Dolah, Mohd Shahrizal; Ramli, Saiful Hasley (Malaysian Public Health Physicians' Association, 2023)
Previous studies have found several discrepancies regarding walking frames/walkers. The purpose of this study was to investigate the issues and challenges that the elderly face when using a walking frame/walker, as well as to identify potential solutions and considerations. The Focus Group Discussion (FGD) and the Quality Function Deployment (QFD) sessions were conducted in this study which involved seventeen respondents from various parties, including people aged 60 and above (current users of walking frames/walkers), their caregivers, industry people involved in the marketing and selling of walking frames/walkers and experts/researchers. Interview data as verbatim transcripts were analyzed thematically and gathered systematically into a specific classification according to the House of Quality (HoQ) for technical analysis. Findings on FGD showed that quality, design, and cost were key issues raised by respondents. Based on the HoQ analysis, it’s indicated that the highest rank of customer requirements (CRs) for a new walking frames/walkers design requirement was safety (rank 1), stable (rank 2), suitable for outdoor use (rank 3), user-friendly (rank 4) and comfort design (rank 5). Meanwhile, the highest rank of technical requirements (TRs) are adjustable height and width (rank 1), design two-level handle walking frames/walkers and design ‘R’ shape walking frames/walkers (rank 2 & 3), design with ABS castor wheel (rank 4) which provided functional accessories such as seat, bucket, and pocket (rank 5). The information acquired would be useful as references for further studies on the development of suitable walking frames/walkers for the Malaysian elderly in the future.